Konstruksi Hukum Terkait Hak atas Kehidupan dan Pekerjaan bagi Pekerja Rumah Tangga berdasarkan Undang-Undang Ketenagakerjaan - Yefiza Nahri Agustia; Irsyaf Marsal (AHKAM, 2025)
The right to work and to a decent livelihood ought to be guaranteed by the state; however, in reality, equal access to formal employment opportunities has yet to be realized, driving many citizens to work as domestic workers under conditions of inadequate wages and benefits. In practice, the majority of domestic workers receive wages below the minimum wage standard and often without guaranteed benefits, reflecting weak protection of their normative rights. This study aims to analyse in depth the implementation of statutory regulations, legal principles, and legal doctrines related to the protection of domestic workers, grounded in a legal policy framework, in order to formulate appropriate policies to safeguard their normative rights. A normative juridical approach is employed through an examination of legislation, legal principles and doctrines, as well as comparative analysis with regulatory frameworks in several countries, such as South Africa and the Philippines, which have enacted specific legislation on domestic workers. The findings show that these countries explicitly regulate minimum wage standards, holiday allowances, maternity leave entitlements, unemployment insurance, and even guarantees of adequate housing for domestic workers, whereas in Indonesia similar regulations remain weak and fragmented. These results indicate the need to revise national policy by setting a minimum wage standard for domestic workers equivalent to the provincial minimum wage, accompanied by sanction mechanisms for violations, so that the protection of wages and benefits becomes fairer and more effective. Accordingly, the strengthening of specific regulations on domestic workers is expected to establish a fair and dignified regulatory framework for domestic workers without neglecting employers’ interests, while simultaneously providing a stronger legal policy foundation for the formulation of domestic labour protection policies in Indonesia.